2002
DOI: 10.1136/bmj.325.7365.636
|View full text |Cite
|
Sign up to set email alerts
|

Married couples' risk of same disease: cross sectional study

Abstract: Objective To determine whether people whose marital partners have depression, diabetes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
2
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(160 citation statements)
references
References 18 publications
4
149
2
5
Order By: Relevance
“…Supporting this idea are analyses of the rates of asthma in genetically unrelated family members. One small study has found its prevalence to be increased in nonallergic, family historynegative spouses of affected adults (12,13), and another has found the rates of asthma to be nearly as high in adopted children of mothers with asthma as in natural children (14).…”
Section: Asthma As a Transmissible Diseasementioning
confidence: 99%
“…Supporting this idea are analyses of the rates of asthma in genetically unrelated family members. One small study has found its prevalence to be increased in nonallergic, family historynegative spouses of affected adults (12,13), and another has found the rates of asthma to be nearly as high in adopted children of mothers with asthma as in natural children (14).…”
Section: Asthma As a Transmissible Diseasementioning
confidence: 99%
“…It was shown earlier that married couples share the occurrence of many common diseases such as hypertension, diabetes, depression, and asthma (Hippisley-Cox et al, 2002). The most likely explanation for that phenomenon, despite selective mating, is a shared lifestyle including diet, physical exercise or environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Maar er zijn ook aanwijzingen dat partners van mensen met een niet-besmettelijke aandoening meer kans lopen om dezelfde aandoening te krijgen. Onderzoek laat zien dat, rekening houdend met leeftijd, roken en overgewicht, partners van mensen met astma, depressie of een maagzweer tenminste 70% meer kans hadden om dezelfde ziekte te krijgen (Hippisley-Cox, Coupland, Pringle, Crown & Hammersley, 2002). Invloeden van genetische overdracht, socialisatie en gezinsomstandigheden blijken niet makkelijk te scheiden, gezinsgelijkenissen ontstaan mede door een combinatie van deze drie mechanismen.…”
Section: Gezinsgelijkenissen In Consultgedragunclassified